Place your bets: psychophysiological correlates of decision-making under risk - Studer, Bettina (Springer-Verlag, 2011)
Emotions and their psychophysiological correlates are thought to play an important role in decision-making under risk. We used a novel gambling task to measure psychophysiological responses during selection of explicitly presented risky options and feedback processing. Active-choice trials, in which the participant had to select the size of bet, were compared to fixed-bet, no-choice trials. We further tested how the chances of winning and bet size affected choice behavior and psychophysiological arousal. Individual differences in impulsive and risk-taking traits were assessed. The behavioral results showed sensitivity to the choice requirement and to the chances of winning: Participants were faster to make a response on no-choice trials and when the chances of winning were high. In active-choice trials, electrodermal activity (EDA) increased with bet size during both selection and processing of losses. Cardiac responses were sensitive to choice uncertainty: Stronger selection-related heart rate (HR) decelerations were observed in trials with lower chances of winning, particularly on active-choice trials. Finally, betting behavior and psychophysiological responsiveness were moderately correlated with self-reported impulsivity-related traits. In conclusion, we demonstrate that psychophysiological arousal covaries with risk-sensitive decision-making outside of a learning context. Our results further highlight the differential sensitivities of EDA and HR to psychological features of the decision scenario.